Thermal record of the building of an orogen in the retro‐foreland basin: Insight from basement and detrital thermochronology in the eastern Pyrenees and the north Pyrenean basin (France). (11th August 2021) - Al Reda, Stéphane M.; Barbarand, Jocelyn; Gautheron, Cécile; Lasseur, Eric; Loget, Nicolas; Pinna‐Jamme, Rosella; Briais, Justine
Abstract: An understanding of the evolution of foreland basins improves our knowledge of how mountain belts have grown and helps us to decipher events which may not be preserved in the orogen. The infilling of the north Pyrenean retro‐foreland basin (Aquitaine Basin, France) during the main exhumation of the Pyrenees and its corresponding thermal history have not been fully investigated. We applied apatite fission track (AFT) and (U‐Th‐Sm)/He (AHe) methods coupled with inverse thermal modelling on both the detrital Eocene (47 to 33 Ma) syn‐orogenic Palassou conglomerates of the eastern part of the Aquitaine Basin and basement samples from the North Pyrenean Zone and the Axial Zone of the Pyrenees. Apatite crystals were separated from granitic cobbles found in the conglomerates. AFT ages for detrital samples range from 27 ± 2 to 43 ± 4 Ma, and AHe ages from 13 ± 1 to 76 ± 5 Ma. For in situ massifs AFT ages range from 35 ± 2 to 90 ± 17 Ma and AHe ages from 39 ± 2 and 80 ± 5 Ma. AFT ages for detrital samples are close to deposition ages, whereas AHe ages are older and younger than deposition ages and show a partial thermal resetting due to burial. A detailed analysis of the ages obtained and thermal histories derived from modelling shows that ages reflect (a) exhumation from 70 to 55 Ma revealed by a long stay in the partial retention zone (PRZ), (b) a Palaeocene–Eocene cooling in the Pyrenees, (c) a post‐depositional episode of moderate heating of the sediments in the basin represented by partially reset young AHe and AFT ages compared to deposition ages and (d) an early to mid‐Miocene final exhumation of the basin deposits as evidenced by young AHe ages and geological constrains. These results reflect a common event with the south Pyrenean foreland basin that is characterized by high piedmont aggradation from the late Eocene to the Miocene. The aggradation of sediments is possibly connected with well‐known high elevation low relief surfaces in the core of the Pyrenees and followed by a Miocene exhumation event that is already observed on the southern flank. However, the timing of the aggradation and exhumation events could be different between the north and the south. Erosion occurred most probably during the early to mid‐Miocene in the north and during the late Miocene–early Pliocene in the south. Abstract : This paper provides new detrital low temperature thermochronology data from the eastern part of the Aquitaine Basin (the Corbières region). Thermal modelling of the obtained results allowed the determination of the thermal history of the samples from their source (the Pyrenees) to the basin (the Corbières region).